Characterisation and In Vitro Drug Release Profiles of Oleanolic Acid- and Asiatic Acid-Loaded Solid Lipid Nanoparticles (SLNs) for Oral Administration - Michael Oboh; Eman Elhassan; Neil Anthony Koorbanally; Laurencia Govender; Muthulisi Siwela; Thirumala Govender; Blessing Nkazimulo Mkhwanazi (Pharmaceutics, 2025)
Objectives: This study characterised and evaluated the stability, solubility, and in vitro drug release of OA- and AA-loaded SLNs. Methods: The OA- and AA-SLNs were formulated using the emulsion solvent evaporation method and characterised based on particle size (PS), polydispersity index (PDI), zeta potential (ZP), and transmission electron microscopy (TEM). Solubility studies were conducted in PBS (pH 1.2 and 6.8) and dH2O using HPLC, while in vitro drug release was assessed in simulated intestinal fluid (SIF) (pH 6.8). Results: The optimised OA-SLNs (1:1 drug-to-lipid ratio) showed PS, PDI, ZP, and EE% values of 312.9 ± 3.617 nm, 0.157 ± 0.014, −17.0 ± 0.513 mV, and 86.54 ± 1.818%, respectively. The optimised AA-SLNs (1:2 drug-to-lipid: ratio) had a PS of 115.5 ± 0.458 nm, PDI of 0.255 ± 0.007, ZP of −11.9 ± 0.321 mV, and EE% of 76.22 ± 0.436%. The SLNs remained stable for 60 days at 4 °C and room temperature (p < 0.05). The solubility study revealed that free OA and AA showed no measurable values in the three solvents. However, OA-SLNs showed the highest solubility in H2O (16-fold) followed by PBS at pH 6.8 (10-fold) and pH 1.2 (10-fold). AA-SLNs significantly improved the solubility in PBS at pH 6.8 (88-fold), compared to dH2O (6-fold) and PBS at pH 1.2 (26-fold). In vitro drug release studies showed that OA release from the SLNs was significantly increased within 300 min (p < 0.05) compared to the free drug. Similarly, AA release from the SLNs was significantly increased within 300 min (p < 0.05) compared to free AA. Conclusions: These results demonstrate that SLNs enhance OA and AA solubility and drug release, suggesting a promising strategy for improving oral bioavailability and therapeutic efficacy.